Diasporic Constructions of Home and Belonging (De Gruyter, 2015)
Diaspora studies has developed in recent years from disparate enquiries into diasporic phenomena in political science, anthropology, history, geography, and literary and cultural studies. Its emergence as a full-fledged transdisciplinary research field has been predicated to a large degree on an interest in questions of dispersal and mobility. Based on the proceedings of an international conference by the Marie Curie Initial Training Network CoHaB, this volume undertakes to shift the focus to phenomena of home-making and the articulation of a sense of belonging in diasporic contexts. Contributors from a broad range of disciplines discuss a variety of historical and geographical instances of diasporas, exploring the methodological and theoretical challenges posed by the subjects of 'home' and 'belonging'. Including an interview with Homi K. Bhabha on these subjects and the place of theory in diaspora studies as well as contributions by such central figures as Pnina Werbner and Ihab Hassan, the volume aims at offering a new prospectus of the range and potential of academic work on the cultural formations of diaspora
10.1515/9783110408614
Keywords: Belonging (Social psychology); Collective memory; Home in literature; Constructions of Home; Cultural studies; Diaspora studies; Postcolonialism; Heimat / Motiv; Literatur; Identität / Motiv; Migration / Motiv; LITERARY CRITICISM / General